The role of the marriage counsellor in a Xhosa community: an exploratory-descriptive study - Phorie, Constancia Lineo (Rhodes University, Faculty of Humanities, Department of Social Work, 1990)
The focus of this study is on the role the marriage counsellor should play in the Black community. This role is being placed in sharp perspective as a result of social change affecting the Black family. Problem-solving, including marriage counselling has traditionally been done by the extended family. This role of the family as a natural support system has been weakened by factors such as urbanization and Westernisation. This has prompted Black couples experiencing in particular marriage problems to make use of professional marriage counselling services from specialised and other welfare agencies. A major problem in the rendering of professional counselling services is that they are to a great extent based on Western civilization as far as basic philosophy and underlying assumptions are concerned. Thus intervention modalities used for marital problems in the Black community do not address the real needs of the people. The main objective of this study was to investigate how marriage counselling services are perceived in the Black community. It is expected that research findings would assist the helping professions make the necessary adjustments to make marriage counselling approaches more relevant to problems experienced in married life in the Black community. The study revealed that the family in the Black community is still regarded as the main problem-solver although people do go beyond the family for assistance. The nuclear family has also started to emerge in the Black community and bonds to the bigger family systems are beginning to loosen. The research findings indicated clearly that there is a need for professional marriage counselling and that services of this nature should be extended further into the Black community. A problem in this regard however is that the community will have to be educated to use these services
Keywords: Marriage counselling -- South Africa; Xhosa (African people) -- Marriage customs and rites; Marriage customs; Family